Membrane reactor immobilized with palladium‐loaded polymer nanogel for continuous‐flow Suzuki coupling reaction. Issue 2 (27th October 2014) - Seto, Hirokazu; Yoneda, Tamami; Morii, Takato; Hoshino, Yu; Miura, Yoshiko; Murakami, Tatsuya
<x xml:space="preserve">Abstract</x> A catalytic membrane reactor, which was immobilized with palladium‐loaded nanogel particles (NPs), was developed for continuous‐flow Suzuki coupling reaction. Palladium‐loaded membranes were prepared by immobilization of NPs, adsorption of palladium ions, and reduction into palladium(0). The presence of palladium in the membrane was confirmed by the scanning electron microscopy; palladium aggregation was not observed. The catalytic activity of the membrane reactor in continuous‐flow Suzuki coupling reaction was approximately double that of a comparable reactor in which palladium ions were directly adsorbed onto an aminated membrane. This was attributed to the formation of small palladium particles. The reusability in the continuous‐flow system was higher than that in a batch system, and the palladium‐loaded membrane reactor had high long‐term stability. © 2014 American Institute of Chemical Engineers AIChE J, 61: 582–589, 2015